2002
DOI: 10.1016/s0014-5793(02)02297-4
|View full text |Cite
|
Sign up to set email alerts
|

Starvation‐induced degradation of yeast hexose transporter Hxt7p is dependent on endocytosis, autophagy and the terminal sequences of the permease

Abstract: The yeast high-affinity glucose transporters Hxt6p and Hxt7p are rapidly degraded during nitrogen starvation in the presence of high concentrations of fermentable carbon sources. Our results suggest that degradation is mainly due to the stimulation of general protein turnover and not caused by a mechanism specifically triggered by glucose. Analysis of Hxt6p/ 7p stability and cellular distribution in end4, aut2 and apg1 mutants indicates that Hxt7p is internalized by endocytosis, and autophagy is involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 30 publications
6
42
0
3
Order By: Relevance
“…Such a mechanism has been described for several yeast sugar transporters, including Hxt5p (van Suylekom et al 2007). In addition, GFP fusions of Hxt2p, Hxt6p, and Hxt7p were degraded in vacuoles by a similar mechanism described in degradation of Hxt5p (Krampe and Boles 2002;Kruckeberg et al 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Such a mechanism has been described for several yeast sugar transporters, including Hxt5p (van Suylekom et al 2007). In addition, GFP fusions of Hxt2p, Hxt6p, and Hxt7p were degraded in vacuoles by a similar mechanism described in degradation of Hxt5p (Krampe and Boles 2002;Kruckeberg et al 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is feasible that Hxts are phosphorylated following treatment with MG prior to endocytosis. Hxt7 lacking the cytoplasmic domain at the N terminus was hardly internalized and degraded under conditions where the endocytosis of Hxt7 was induced (high glucose conditions) (51). It has been reported that the PEST (Pro-Glu-Ser-Thr) sequence found at the N terminus of Hxt7 is involved in the degradation (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The Hxtp hexose transporters that play a key role in the control of sugar flux in fermentation are controlled in this way (Krampe and Boles 2002). This mechanism, in combination with transcriptional control, modulates the abundance of Hxtp carriers in the plasma membrane (Perez et al 2005).…”
Section: Effect Of Starvation On Protein Fate and Amino Acid Homeostasismentioning
confidence: 99%